Examining Muscle Activity Differences During Single and Dual Vector Elastic Resistance Exercises - Ryan WG Bench; Sydney E Thompson; Alan C Cudlip; Michael WR Holmes (International Journal of Sports Physical Therapy)
# Background Elastic resistance exercise is a common part of rehabilitation programs. While these exercises are highly prevalent, little information exists on how adding an additional resistance vector with a different direction from the primary vector alters muscle activity of the upper extremity.